2021
DOI: 10.1186/s43159-021-00114-7
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal submucosal lipoma: a rare cause of secondary intussusception in a child

Abstract: Background Intestinal lipomas are benign, non-epithelial, intestinal tumors with an exceptionally rare localization at the ileum. Lipomas in the small intestine occur mainly in elderly patients and seldom occur in childhood. They are frequently asymptomatic, possibly due to their slow growth. These tumors may act as a lead point of intussusception. Case presentation We report a rare case of double compounded ileo-ileal intussusception due to a subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…17 In longitudinal view, peripheral hypoechoic and central echogenic area is seen, termed as pseudokidney sign. 18 Central echogenecity of pseudokidney sign is contributed by mesentery due to its fat content. Color Doppler study has an important role in detection of bowel viability.…”
Section: Resultsmentioning
confidence: 99%
“…17 In longitudinal view, peripheral hypoechoic and central echogenic area is seen, termed as pseudokidney sign. 18 Central echogenecity of pseudokidney sign is contributed by mesentery due to its fat content. Color Doppler study has an important role in detection of bowel viability.…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal lipomas, although rare, have been previously reported to cause intussusception in children. [ 4 ] There are three pathological types of intestinal lipomas: (i) intermuscular type; (ii) subserosal type; and (iii) submucosal type. The tumors arise from the submucosa in 90% of cases, while the remainders are usually subserosal.…”
Section: Discussionmentioning
confidence: 99%
“…The tumors arise from the submucosa in 90% of cases, while the remainders are usually subserosal. [ 4 ] In a systematic review of 147 cases of small bowel lipoma over 20 years, there were 138 adults and only 9 children with small bowel lipomas. [ 5 ] For pediatric age group, small intestinal lipomas, median age at diagnosis is 8 years with a range from 4 to 14 years and highly echoic masses on ultrasound or appear as round or oval, well-defined, hypointense, and intraluminal masses on computed tomography scans.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually difficult to identify and diagnose before surgery. Cheikhrouhou et al mentioned that only 7 cases of intussusception due to lipoma in pediatric patients were reported so far, with a median age of 8 years [ 3 ]. Manouras et al showed that lesions smaller than 1 cm are considered asymptomatic, and lipomas are more likely to be symptomatic when the diameter exceeds 2 cm.…”
Section: Discussionmentioning
confidence: 99%